Anti-microbial Activities of Syzigium cumini leaves against Periodontophatic Bacteria (Porphyromonas gingivalis) - Praptiwi, Yenni Hendriani; Heriyanto, Yonan; Widyastuti, Tri; Sukmasari, Susi (Gaceta Médica de Caracas, 2023)
Introduction: Syzigium cumini has been known to have an anti-microbial effect and is traditionally used as medicine for some human diseases. However, only a few studies were done on water extracts of these leaves. This study aimed to elucidate the minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) of water extract of Syzigium cumini leaves against Porphyromonas gingivalis that represent periodontopathic bacteria.